Chemical vapor deposition of germanium-rich CrGex nanowires - Dřínek, Vladislav; Tiagulskyi, Stanislav; Yatskiv, Roman; Grym, Jan; Fajgar, Radek; Jandová, Věra; Koštejn, Martin; Kupčík, Jaroslav (Beilstein Journal of Nanotechnology, 2021)
Chemical vapor deposition was applied to synthetize nanostructured deposits containing several sorts of nanoobjects (i.e., nanoballs, irregular particles, and nanowires). Analytical techniques, that is, high-resolution transmission electron microscopy, scanning electron microscopy, electron dispersive X-ray analysis, selected area electron diffraction, and X-ray photoelectron spectroscopy, showed that unlike nanoballs and particles composed of crystalline germanium, the layer was made of chromium germanide CrGex. The nanowires possessed a complex structure, namely a thin crystalline germanium core and amorphous CrGex coating. The composition of the nanowire coating was [Cr]/[Ge] = 1:(6–7). The resistance of the nanowire–deposit system was estimated to be 2.7 kΩ·cm using an unique vacuum contacting system.
Keywords: chemical vapor deposition; chromium germanide; nanostructured materials; nanowire; resistivity

"Direct process" - Wikipedia contributors (Wikipedia, The Free Encyclopedia)

(untitled) - Jandl, I.; Richter, K. W. (J. Alloys Compd., 2010)

(untitled) - Li, M.; Guo, C.; Li, C.; Du, Z. (J. Alloys Compd., 2009)

(untitled) - Neddermann, R.; Wartchow, R.; Binnewies, M. (Z. Anorg. Allg. Chem., 1998)

(untitled) - Caillat, T.; Fleurial, J.-P.; Borshchevsky, A. (J. Alloys Compd., 1997)

(untitled) - Ahmed, A. S.; Esser, B. D.; Rowland, J.; McComb, D. W.; Kawakami, R. K. (J. Cryst. Growth, 2017)

(untitled) - Dhaka, K.; Bandyopadhyay, D. (Adv. Sci. Lett., 2014)

Introduction to the Physics of Diluted Magnetic Semiconductors - Kossut, J.; Gaj, J. A. (Springer, 2000)

(untitled) - Morgunov, R. B.; Dmitriev, A. I.; Tanimoto, Y.; Kazakova, O. (J. Appl. Phys., 2009)

(untitled) - Katkar, A. S.; Chu, Y.-C.; Chu, L.-W.; Chen, L.-J. (Cryst. Growth Des., 2011)

(untitled) - Goswami, R.; Kioseoglou, G.; Hanbicki, A. T.; Jonker, B. T.; Spanos, G. (Acta Mater., 2004)

(untitled) - Dřínek, V.; Klementová, M.; Fajgar, R.; Dytrych, P. (Mater. Lett., 2015)

(untitled) - Biesinger, M. C.; Payne, B. P.; Grosvenor, A. P.; Lau, L. W. M.; Gerson, A. R.; Smart, R. S. C. (Appl. Surf. Sci., 2011)

(untitled) - Pfau, A. J.; Diulus, J. T.; He, S.; Albuquerque, G. H.; Stickle, W. F.; Herman, G. S. (Appl. Surf. Sci., 2019)

(untitled) - ThermoFisher Scientific

(untitled) - Hierlemann, M.; Simka, H.; Jensen, K. F.; Utz, M. (J. Phys. IV, 1995)

(untitled) - Weckhuysen, B. M.; Rao, R. R.; Pelgrims, J.; Schoonheydt, R. A.; Bodart, P.; Debras, G.; Collart, O.; Van Der Voort, P.; Vansant, E. F. (Chem. – Eur. J., 2000)

(untitled) - Schmidt, V.; Gösele, U. (Science, 2007)

(untitled) - Schlexer, P.; Andersen, A. B.; Sebok, B.; Chorkendorff, I.; Schiøtz, J.; Hansen, T. W. (Part. Part. Syst. Charact., 2019)

(untitled) - Perea, D. E.; Hemesath, E. R.; Schwalbach, E. J.; Lensch-Falk, J. L.; Voorhees, P. W.; Lauhon, L. J. (Nat. Nanotechnol., 2009)

(untitled) - Hanrath, T.; Korgel, B. A. (J. Phys. Chem. B, 2005)

(untitled) - Lauwaert, J.; Van Gheluwe, J.; Vanhellemont, J.; Simoen, E.; Clauws, P. (J. Appl. Phys., 2009)

(untitled) - Mohammad, S. N. (J. Chem. Phys., 2007)